Role of executive functioning and literary reapproach for measures of intelligence - Hania, Alishba; Orcullo, Daisy Jane C.; Zubir, Azlizamani (IJHSSI, 2017)
Over the years, Intelligence has been a crucial part in Psychological practices.Basic operational definition behind construct of Intelligence proposed by Wechsler (1944), was to act purposefully (Plan and control behaviors) and thinking rationally (organize and direct behavior). This operational definition was afterwards incorporated in measures for intelligence but as these measures were first aligned with academics, a major part of basic definition got overlooked. Previously Intelligence was divided in two major components that are Crystalized and Fluid Intelligence but resent Literary Reaproach was intended to enlighten the basic purpose of Intelligence measures and to highlight the overlooked components of Intelligence.These components are then further aligned with behavioral interpretations of Executive functions.It is proposed that alliance of Fluid Intelligence with Executive Functioning can bring pronounced change in clinical practices and change the bookish views of Intelligence into a functional approach.